2013
DOI: 10.1016/j.jmbbm.2012.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan membranes containing micro or nano-size bioactive glass particles: evolution of biomineralization followed by in situ dynamic mechanical analysis

Abstract: A new family of biodegradable polymer/bioactive glass (BG) composite materials has emerged based on the availability of nano-sized bioactive particles. Such novel biocomposites can have enhanced performance, in terms of mechanical properties and bioactivity, and they can be designed to be used in bone regeneration approaches. In this work, membranes of chitosan (CTS) and chitosan with bioactive glass (BG) both micron and nano sized particles (CTS/μBG, CTS/nBG, respectively) were prepared by solvent casting. Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(57 citation statements)
references
References 55 publications
6
48
0
3
Order By: Relevance
“…These findings are consistent with results obtained in our previous works [25,26], as well as those of other authors [52,53]. Moreover, it was shown that the larger surface area of smaller glass particles provides more effective ion release, enhancing the ability of HAp layer formation on the composite surfaces [22].…”
Section: In Vitro Degradationsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are consistent with results obtained in our previous works [25,26], as well as those of other authors [52,53]. Moreover, it was shown that the larger surface area of smaller glass particles provides more effective ion release, enhancing the ability of HAp layer formation on the composite surfaces [22].…”
Section: In Vitro Degradationsupporting
confidence: 93%
“…New bands can be assigned to O-P-O bending mode and P-O stretching mode, respectively. Furthermore, new absorption band corresponding to the carbonate groups CO 3 2-in HCA was found at 873 cm -1 (outof-plane bending mode) [22]. In the case of A2-PCL composite films, the almost complete vanishing of bands characteristic for PCL was observed after incubation, confirming high thickness and uniformity of the formed CaP layer.…”
Section: In Vitro Bioactivitymentioning
confidence: 78%
“…Jaakkola et al [51] and Caridade et al [31] observed that faster consumption of both Ca and P, as well as faster release of Si occurred in case of composites containing smaller BG particles size. Apart from Ca release/consumption profiles affected by above-mentioned compensation process, these findings correlate with results obtained in present work only for materials produced with the use of TIPS method.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, the larger surface area of BG particles allows a faster ion exchange with the surrounding medium enhancing ability of HAp layer formation on the composite surfaces [31]. Our previous studies indicated that the uniform distribution of smaller BG particles (A2\3 μm) in the PCL matrix of solvent-cast films resulted in crystallization of carbonated hydroxyapatite (HCA) on the AS surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation